Telegram as Social Networking Service (SNS) For Enhancing Students’ English: A Systematic Review - Citrawati, Ni Kadek; Suwastini, Ni Komang Arie; Jayantini, I Gusti Agung Sri Rwa; Artini, Ni Nyoman; Dantes, Gede Rasben (Yayasan Visi Intan Permata, 2021)
Social Networking Services (SNS) has become part of English learning, providing educators and students with free service and wide usage applicable to synchronous and asynchronous instruction. This study intended to critically review previous studies on the use of Telegram as one of the SNS platforms for enhancing students' reading, writing, speaking, and listening skills. Following George’s (2008) Literature Reviews model, 20 manuscripts were reviewed. The selection was taken from reputable International Journals indexed by Scopus quartile 1, 2, and 3, published between 2016-2020. It was revealed that Telegram is argued to have positively affect the students' four language skills in learning English. Telegram is claimed to benefit the students in terms of vocabulary, reading comprehension, content, and organization in writing, grammar, language style, pronunciation, and listening comprehension. Experts highlighted the relaxed and informal nature of Telegram as SNS to be one of the main factors that contributed positively to students' reduced anxiety and raised motivation in learning. Reflecting on those positive effects of Telegram on students' scholastics progress, the present study implies that Telegram may be an alternative for online learning and extensive learning of English.